2013
DOI: 10.1038/nrc3582
|View full text |Cite
|
Sign up to set email alerts
|

Krüppel-like factors in cancer

Abstract: Krüppel-like factors (KLFs) are a family of DNA-binding transcriptional regulators with diverse and essential functions in a multitude of cellular processes, including proliferation, differentiation, migration, inflammation and pluripotency. In this Review, we discuss the roles and regulation of the 17 known KLFs in various cancer-relevant processes. Importantly, the functions of KLFs are context dependent, with some KLFs having different roles in normal cells and cancer, during cancer development and progress… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
331
0
5

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 336 publications
(348 citation statements)
references
References 200 publications
12
331
0
5
Order By: Relevance
“…Statistical analyses of the differentially expressed genes bound by KLF9 proximal to TSS showed that KLF9 functions primarily as a transcriptional repressor in the context of glioma neurospheres. This does not absolutely rule out the possibility that KLF9 has transactivating activity under defined biological contexts, particularly given the strong influence of biological context and genetic background on the gene regulatory activities, including those of KLF family members (24,55). A particularly relevant example is from Mitchell and DiMario (56), who found that KLF9 transactivated an FGFR1 promoterreporter construct in human myoblasts but repressed the same reporter in differentiated myotubes.…”
Section: Discussionmentioning
confidence: 99%
“…Statistical analyses of the differentially expressed genes bound by KLF9 proximal to TSS showed that KLF9 functions primarily as a transcriptional repressor in the context of glioma neurospheres. This does not absolutely rule out the possibility that KLF9 has transactivating activity under defined biological contexts, particularly given the strong influence of biological context and genetic background on the gene regulatory activities, including those of KLF family members (24,55). A particularly relevant example is from Mitchell and DiMario (56), who found that KLF9 transactivated an FGFR1 promoterreporter construct in human myoblasts but repressed the same reporter in differentiated myotubes.…”
Section: Discussionmentioning
confidence: 99%
“…29 To evaluate the correlation of other KLFs in TCGA lung adenocarcinoma, we analyzed mRNA expression level of KLF1-17 in adenocarcinoma patients and found that in addition to KLF4, KLF1, 2, 6, 8, 9, 10, 11, 12, 13, 14, 15 and 17 were also significantly lower in tumor compared with normal tissues (Supplementary Figure 2).…”
Section: Resultsmentioning
confidence: 99%
“…In addition to KLF4, other members of KLF family can be altered in lung cancers 29 ( Supplementary Figure 2). It is of great interest to further study the function of other KLF transcription factors in lung tumor initiation and progression.…”
mentioning
confidence: 99%
“…In addition to the well-known functions of Klf4/5 in mammalian embryonic stem cells, other Klf proteins have been implicated in the regulation of cell proliferation, differentiation, and apoptosis and, hence, are essential for tissue and organ development. Aberrant expression of klf genes are linked to various diseases including cancers (Pearson et al, 2008;Cao et al, 2010;McConnell and Yang, 2010;Tetreault et al, 2013). A few studies so far have revealed that certain members in the Klf family are involved in early embryonic development through sea urchin to mouse (Howard et al, 2001;Gardiner et al, 2005;Yamazaki et al, 2008;Caiazzo et al, 2010;Lin et al, 2010;Kotkamp et al, 2014).…”
Section: Introductionmentioning
confidence: 99%